Does Environment Uncertainty Affect Earnings Management? - Gloria Putri Naftali Surbakti; Erina Sudaryati (Jurnal Reviu Akuntansi dan Keuangan, 2021)
This research is aimed to examine the effect of environment uncertainty towards earnings management. This study is a quantitative study with sample all of manufacturing companies that are listed in Indonesian Stock Exchange (IDX) from period 2013 -2018 and publish the financial statement consecutively during period 2013-2018. The sample is selected by using purposive sampling techniques with total of 455 companies. This study uses secondary data that derived from the financial statements of manufacturing companies during that period. By using regression analysis and SPSS in processing research data, the study finds that environment uncertainty has positive impact to financial distress. It indicates when companies are facing an environment uncertainty, it will impact to their performance especially financial performance which leads to the financial distress condition. Companies in higher financial distress condition are more likely to manage their earnings by using earnings management which are measured by discretionary accruals. This research is useful for investor as one of consideration before making financial decision especially when companies are in uncertain environment.